The MODEL PARTISIPASI POLITIK MASYARAKAT SUMATERA BARAT DALAM PILPRES TAHUN 2019 - Noval Prasetyo; Asrinaldi Asrinaldi; Aidinil Zetra (Komisi Pemberantasan Korupsi, 2022)
Levels of voter participation in West Sumatra for the 2019 Presidential Election increased, accompanied by increased scores in corruption perception and life satisfaction. This study aims to determine the relationship between corruption perceptions, life satisfaction, and political participation. The approach used is a quantitative survey method, with the number of respondents being 1000 voters in the 2019 Presidential Election. This research has found that the levels of political participation in West Sumatra are considered quite good. However, this finding is also a warning to the government and its apparatus because only six points above average. This warning also applies to candidates, political parties who propose candidates, as well as existing political systems and institutions which aid in implementing the people's will (democracy).